Optimization of Warehouse Selection with SWOT and AHP Methods in the Pulogadung Industrial Area - Abdulah Rakhman; Tumpal Janji Raja Sitinjak; Tony Sitinjak (International Journal of Social Science and Business, 2023)
This study aims to analyze the factors that influence the determination of location and warehouse space in Pulogadung Industrial Estate, Jakarta, using a combined SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) and AHP (Analytical Hierarchy Process). The research method applied is qualitative. Participants in this study were leaders of companies operating in the Pulogadung Industrial Estate. Data was collected through the use of SWOT questionnaires and AHP questionnaires given to respondents. SWOT data is analyzed using Excel software, while AHP data is analyzed using Super Decision software. The results revealed that factors that affect the determination of warehouse location and space in the Pulogadung Industrial Estate include proximity to the main road, centralized warehouse location, proximity to the goods distribution terminal, proximity to the port, and efficiency of warehouse maintenance costs. SWOT and AHP analysis show the importance of the determinants of the location of the Pulogadung Industrial Estate, Jakarta. The most important "strength" factor is the location of the warehouse close to the main road, while the "weakness" factor that needs to be avoided is the high cost of renting the warehouse. The "opportunity" factor that must be exploited is the application of modern technology, and the "threat" factor that needs to be avoided is the emergence of more efficient warehouse maintenance costs in competitors' warehouses. This research provides important insights for companies operating in the Pulogadung Industrial Estate in determining the location of their warehouses.